Mrs. Dred Scott a life on slavery's frontier - VanderVelde, Lea (Oxford University Press, 2009)
In telling the life of Harriet, Dred's wife and co-litigant in the case, this book provides a compensatory history to the generations of work that missed key sources only recently brought to light. Moreover, it gives insight into the reasons and ways that slaves used the courts to establish their freedom. --from publisher description.